Challenging Gender Inequality through Female Empowerment in Uzma Jalaluddin’s Ayesha at Last - Nayu, Tasya Oktadila; Djohar, Hasnul Insani (Lakon : Jurnal Kajian Sastra dan Budaya, 2025)
This research explores how gender inequality and resistance are portrayed in Ayesha at Last, a novel by Uzma Jalaluddin. The main character, Ayesha, is a Muslim woman living in Canada who faces social pressure to follow traditional gender roles. Using Mansour Fakih’s theory, the research identifies different forms of gender inequality in Ayesha’s life, such as stereotypes, subordination, symbolic violence, marginalization, and double burden. At the same time, using bell hooks’ theory of feminist empowerment, the research also shows how Ayesha resists these pressures. She expresses her voice, chooses her career, wears the hijab with pride, and makes personal decisions based on her values. The method used is close textual analysis (CTA), focusing on the language and actions in the novel. This research aims to show that even small, everyday choices can be powerful acts of resistance, especially for Muslim women living in diaspora communities. The research contributes to a deeper understanding of how literature can reflect and challenge gender injustice.